The Analysis Study of Effect of Vitamin D Supplementation to Cognition in Older Adults : A Comprehensive Systematic Review - Intan Ayuningtyas; Radiasti Maharani; Risca Hijrianti; Charles Sanjaya Seikka (International Medical Journal Corp. Ltd, 2025)
Background: Cognitive decline is a significant public health concern among older adults, affecting memory, executive function, and overall quality of life. This systematic review aims to provide a comprehensive analysis of the current evidence on the effects of vitamin D supplementation on cognition in older adults. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2015 to 2025. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: Vitamin D supplementation shows potential in improving cognitive function in older adults, especially those with insufficiency or impairments. However, further research with larger, long-term trials is needed to define optimal doses, timing, and cognitive domains for supplementation benefits.